Pengaruh Gaya Kepemimpinan, Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Surya Logistik Internasional - Nabila Widia Agustin; Nor Lailla (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpse og this study was to determine the influence of leadership style, compensation and work environment on emplpyee performace at PT. Surya Logistik Internasional. The population and sapmle in this study were 50 employee of PT. Surya Logistik Internasional. The sampel in this study used a non-probability sampling technique or saturated sample. Yhe type of data in this study were primary and seconedary data. Data collection was carried out by distributing questionnaires via Google Form. The results of this study indicate that leadership style has a significant effect on employee performance, compensation and work environment have no significant effect on employee performance.